Arabidopsis RING‐type E3 ubiquitin ligase XBAT35.2 promotes proteasome‐dependent degradation of ACD11 to attenuate abiotic stress tolerance. (18th November 2020) - Li, Qiaomu; Serio, Renata J.; Schofield, Andrew; Liu, Hongxia; Rasmussen, Sheena R.; Hofius, Daniel; Stone, Sophia L.
SUMMARY: Plants employ multiple mechanisms to cope with a constantly changing and challenging environment, including using the ubiquitin proteasome system (UPS) to alter their proteome to assist in initiating, modulating and terminating responses to stress. We previously reported that the ubiquitin ligase XBAT35.2 mediates the proteasome‐dependent degradation of Accelerated Cell Death 11 (ACD11) to promote pathogen defense. Here, we demonstrate roles for XBAT35.2 and ACD11 in abiotic stress tolerance. As seen in response to pathogen infection, abiotic stress stabilizes XBAT35.2 and the abundance of ACD11 rose consistently with increasing concentrations of abscisic acid (ABA) and salt. Surprisingly, exposure to ABA and salt increased the stability of ACD11, and the overexpression of ACD11 improves plant survival of salt and drought stress, suggesting a role for ACD11 in promoting tolerance. Prolonged exposure to high concentrations of ABA or salt resulted in ubiquitination and the proteasome‐dependent degradation of ACD11, however. The stress‐induced turnover of ACD11 requires XBAT35.2, as degradation is slowed in the absence of the E3 ubiquitin ligase. Consistent with XBAT35.2 mediating the proteasome‐dependent degradation of ACD11, the loss of E3 ubiquitin ligase function enhances the tolerance of salt and drought stress, whereas overexpression increases sensitivity. A model is presented where, upon the perception of abiotic stress, ACD11 abundance increases to promote tolerance. Meanwhile, XBAT35.2 accumulates and in turn promotes the degradation of ACD11 to attenuate the stress response. The results characterize XBAT35.2 as an E3 ubiquitin ligase with opposing roles in abiotic and biotic stress. Significance Statement: Ubiquitin ligases are the substrate‐selecting component of the essential ubiquitin proteasome system. Arabidopsis RING‐type ubiquitin ligase XBAT35.2 was previously reported to promote pathogen defense via mediating the proteasome‐dependent degradation of ACD11. Here, ACD11 is shown to promote salt and drought tolerance, whereas stress‐stabilized XBAT35.2 targets ACD11 for degradation to attenuate the abiotic stress responses. This report identifies XBAT35.2 as a ubiquitin ligase with multiple and opposing roles in plant responses to biotic and abiotic stresses.